PERANCANGAN DASHBOARD UNTUK PEMANTAUAN TERHADAP KEBUTUHAN PEMBELIAN MATERIAL PADA PT XYZ MENGGUNAKAN METODE OLAP - Glenvin Kiamidi; Wasino; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
This XYZ company is engaged in Agribusiness. In the process of coconut processing palm oil needs the help of materials such as iron, steel, and so on. The data to be processed from this company is material purchasing data. Of course, processing this data requires an application from the business intelligence or commonly abbreviated as Business Intelligence or BI. Deployed BI application is a dashboard to display the amount of material purchases along with targets, Order Unit, Category, Location, and Date. The process is created with perform ETL processing on OLTP, and OLAP data. Then will make dashboard using Power BI which is then uploaded to the website so that it can be accessed by users online. In this research method using the OLAP method. This OLAP method aims to analyze deeper data regarding the year, month, and date. Analyze in more detail using drilldown. The drilldown is used in order to be able to analyze in detail the amount of material purchase requirements which will be analyzed in more depth regarding the achievement of material purchasing needs. The final result of this research is a dashboard. This can be used as a reference by the user for material monitoring and analysis